Wonder Woman. Vol. 1, Outlaw - King, Tom, 1978- (DC Comics, 2024)
"After a shocking alleged crime, the U.S. government moves to keep all Amazons out of the country. What will Wonder Woman discover when she goes on a quest to uncover the truth? And what new enemies will reveal themselves? After a mysterious Amazonian is accused of mass murder, the U.S. Congress passes The Amazon Safety Act, barring all Amazons from American soil. To carry out its new law, the government sets up the Amazon Extradition Entity (AXE) task force to remove those who don't comply by any means necessary. In her search for the truth behind the killing, Wonder Woman now finds herself an outlaw in the world she once swore to protect"--